DEVELOPMENT OF SOUND ABSORBER BASED ON MICROSLIT PANEL ABSORBER CONSIDERING VARIATIONS OF SLIT PATTERNS - Dzul Rasul, Zahra
The Microperforated Panel (MPP) is recognized as an alternative sound absorber. This system consists of a panel with a set of holes smaller than 1 mm in diameter (d < 1 mm). One challenge in applying MPP is the need for precision manufacturing equipment to create thousands of sub-millimeter holes in a small area, where high potential inaccuracy can lead to variations in the panel's absorption performance. To simplify the design and reduce inaccuracies in the fabrication process, the Microslit Panel (MSP) has been developed by replacing circular holes with elongated slits. MSP offers similar sound absorption capabilities to MPP configurations but with a simpler manufacturing process. Furthermore, exploration on variations of slit patterns, such as zigzag, meander, and spiral designs, has been conducted to expand MSP's practical applications, for example, in interior building design. Therefore, this research focuses on developing a model to predict the absorption behavior of MSP with straight and non-straight slit patterns, exploring the effect of MSP's physical parameters on sound absorption performance, designing MSP configurations to achieve a broader sound absorption range, and validating the obtained sound absorption performance with experimental results. The influence of physical parameters on panel absorption performance has been obtained through parametric studies. Experimental validation proves that the Maa model for the default straight slit patterns can be applied to other patterns with low perforation ratios and consistent slit spacing. The absorption performance of parallel MSP configurations has been shown to broaden the half-absorption bandwidth by 1,48 times compared to a single configuration. Experimental validation proves absorption curve similarity and an average MAE of 11.7% across all sixteen samples.